Green and Innovative Extraction: Phenolic Profiles and Biological Activities of Underutilized Plant Extracts Using Pulsed Electric Fields and Maceration - Noelia Pallarés; Houda Berrada; Emilia Ferrer; Wahiba Rached; José Pinela; Filipa Mandim; Tania C. S. P. Pires; Tiane C. Finimundy; Francisco J. Barba; Lillian Barros (Foods)
Underutilized plant species such as Asteriscus graveolens (Forssk.) Less., Haloxylon scoparium Pomel, and Ruta chalepensis L. have been historically valued in traditional medicine for their potential health benefits. These species present an untapped source of bioactive compounds with significant applications in the food and pharmaceutical industries, including the development of functional foods and additives. Recent advances in food processing have introduced innovative methods, such as pulsed electric fields (PEFs), to enhance the extraction of valuable compounds without compromising their integrity or quality. This study investigates the impact of PEF technology on the recovery of bioactive compounds from these plants, comparing it with conventional maceration (MAC) techniques. Phenolic compound profiles and biological activities, including antioxidant, antimicrobial, anti-inflammatory, and cytotoxic effects, were evaluated. The results demonstrated that for R. chalepensis, PEF extraction achieved comparable phenolic content (58 mg/g) to MAC (72 mg/g). However, MAC generally provided higher phenolic yields for other plants. A. graveolens extracts exhibited significant antitumoral and anti-inflammatory potentials. The antimicrobial results indicated that MAC extracts were more effective against bacterial growth, while PEF extracts outperformed MAC against A. brasiliensis (MIC: 10 mg/mL). Antioxidant potential was observed in both methods, with TBARS IC50 values ranging from 17 to 79.5 µg/mL. While MAC generally yielded superior results, PEF extraction showed great promise as an environmentally sustainable alternative, eliminating the need for organic solvents and aligning with green extraction principles.